A comparison of hand-arm vibration syndrome between Malaysian and Japanese workers - Ting, Anselm Su; Fukumoto, Jin; Azlan, Darus; Hoe, Victor CW; Miyai, Nobuyuki; Marzuki, Isahak; Takemura, Shigeki; Awang, Bulgiba; Yoshimasu, Kouichi; Maeda, Setsuo; Miyashita, Kazuhisa (Japan Society for Occupational Health, 2013)
A Comparison of Hand-arm Vibration Syndrome between Malaysian and Japanese Workers: Anselm Ting SU, et al. Centre for Occupational and Environmental Health, Department of Social and Preventive Medicine, University of Malaya, Malaysia-The evidence on hand-arm vibration syndrome (HAVS) in tropical environments is limited. The legislation for the control of occupational vibration exposure has yet to be established in Malaysia. Objectives: The aim of this study was to investigate the clinical characteristics of HAVS in a tropical environment in comparison with a temperate environment. Methods: We conducted a series medical examinations among the forestry, construction and automobile industry workers in Malaysia adopting the compulsory medical examination procedure used by Wakayama Medical University for Japanese vibratory tools workers. We matched the duration of vibration exposure and compared our results against the Japanese workers. We also compared the results of the Malaysian tree fellers against a group of symptomatic Japanese tree fellers diagnosed with HAVS. Results: Malaysian subjects reported a similar prevalence of finger tingling, numbness and dullness (Malaysian=25.0%, Japanese=21.5%, p=0.444) but had a lower finger skin temperature (FST) and higher vibrotactile perception threshold (VPT) values as compared with the Japanese workers. No white finger was reported in Malaysiansubjects. The FST and VPT of the Malaysian tree fellers were at least as bad as the Japanese tree fellers despite a shorter duration (mean difference=20.12 years, 95%CI=14.50, 25.40) of vibration exposure. Conclusions: Although the vascular disorder does not manifest clinically in the tropical environment, the severity of HAVS can be as bad as in the temperate environment with predominantly neurological disorder. Hence, it is essential to formulate national legislation for the control of the occupational vibration exposure.